Orbifolds and finite group representations - Li Chiang; Shi-Shyr Roan (International Journal of Mathematics and Mathematical Sciences)
We present our recent understanding on resolutions of Gorenstein orbifolds, which involves the finite group representation theory. We concern only the quotient singularity of hypersurface type. The abelian group Ar(n) for A-type hypersurface quotient singularity of dimension n is introduced. For n=4, the structure of Hilbert scheme of group orbits and crepant resolutions of Ar(4)-singularity are obtained. The flop procedure of 4-folds is explicitly constructed through the process.